Hereditary predisposition syndromes to myeloid neoplasms: diseases, genes and mechanisms of development - M. V. Makarova; M. V. Nemtsova; D. A. Chekini; D. K. Chernevskiy; O. V. Sagaydak; E. V. Kosova; A. A. Krinitsyna; M. S. Belenikin; P. A. Zeynalova (Онкогематология, 2024)
With the development of modern next generation sequencing based DNA diagnostic methods, it has become possible to study hereditary predisposition to oncohematological diseases. Germline variants (mutations) of RUNX1, CEBPA, GATA2, ANKRD26, DDX41, FANC- (Fanconi anemia), etc. genes, associated with the development of hereditary hematological malignancies, have been identified. Timely diagnosis of such diseases will allow for medical genetic counseling and testing of the patient’s relatives to identify or exclude the risk of developing the disease, select a donor for the patient (it is undesirable to use a mutation carrier relative as a donor), and personalize the choice of chemotherapy regimens (for example, patients with Fanconi anemia may experience increased sensitivity to chemotherapy). The aim of this review is to present a modern view of the genetic predisposition to the development of hematological malignancies.